Facial type measurements influence on transverse dimensions of normal occlusion arches - Gallão, Simone; Faltin Júnior, Kurt; Santos-Pinto, Lourdes [UNESP]; Santos-Pinto, Ary dos [UNESP]; Martins, Lídia Parsekian [UNESP] (My University, 2013)
Objective – To correlate facial type measurements of Caucasian individuals with transverse dimensions of normal occlusion arches. Methods – Twenty-one pairs of dental models were selected according to the following inclusion criteria: presence of all permanent teeth from 1 st molar to 1 st molar; normal occlusion; no prosthetic crowns; no previous orthodontic treatment and 2 mm or less of crow- dings or spacings. The cephalometric measurements of lateral cephalometric X-ray of the same individuals were taken and tabulat ed. To evaluate the repetition of arch measurements, paired Student’s t-test and Pearson's correlation coefficient were used. The r elationship between the measurements was analysed by using the Pearson’s correlation. Results – The repetition of the measurements showed high correlation and no systematic error. In the comparison between the measurements, a moderate negative correlation was observed b et- ween facial axis angle and the measurements Upper and Lower 6-6, whereas a positive correlation was observed between dentition height and the latter. Conclusion – It was observed a negative correlation between facial axis angle and upper and lower inter-molar distance as well as a positive correlation between dentition height and upper and lower inter-molar distance.

Objetivo – Correlacionar medidas do tipo facial, em indivíduos leucodermas, com dimensões transversas das arcadas em oclusão normal. Métodos – Vinte e um pares de modelos de gesso foram selecionados de acordo com os requisitos de inclusão: presença de todos os dentes permanentes de 1° molar a 1° molar; oclusão normal; sem coroas protéticas; nenhum tratamento ortodôntico prévio e apinhamentos ou es- paçamentos menores ou iguais a 2 milímetros. As medidas cefalométricas das telerradiografias laterais destes mesmos indivíduos foram consultadas e tabuladas. Para a avaliação da repetibilidade das medidas das arcadas foram utilizados o teste t de Student parea do e o coe- ficiente de Pearson. O grau de associação entre as medidas foi analisado pelo coeficiente de correlação de Pearson. Resultados – A repeti- bilidade de medidas demonstrou alta correlação e ausência de erro sistemático. Na comparação entre as medidas houve correlação negativa moderada do ângulo do eixo facial com as medidas Sup 6-6 e Inf 6-6 e correlação positiva da altura da dentição com as medidas S up 6-6 e Inf 6-6. Conclusão – Houve correlação negativa entre ângulo do eixo facial e as distâncias intermolares superiores e inferiores e, correlação positiva entre a altura da dentição e as distâncias intermolares superiores e inferiores.
Influência das medidas do tipo facial nas dimensões transversas das arcadas em oclusão normal
Keywords: Face; Dental models; Dental arch; Face; Modelos dentários; Arco dental